2021
DOI: 10.1002/mgg3.1653
|View full text |Cite
|
Sign up to set email alerts
|

Total number of reads affects the accuracy of fetal fraction estimates in NIPT

Abstract: Background Sufficient fetal fraction (FF) is crucial for quality control of NIPT (Non‐Invasive Prenatal Test) results. Different factors influencing bioinformatic estimation of FF should be considered when implementing NIPT. To what extent the total number of sequencing reads influences FF estimate has been unexplored. In this study, to test the robustness of SeqFF FF estimation and provide additional recommendations for NIPT analysis quality control, we compared the SeqFF FF estimates with two other methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Moreover, depending on the software used for FF calculation, FF estimator accuracy can fall at low sequencing coverages in cases of truly low FFs ( Figs 3 and S6 ). Similar results were obtained by Miceikaitė et al ., who demonstrated that FF estimator accuracy tends to decrease at low sequencing depths [ 16 ]. Severe FF estimation inaccuracies can lead to the inappropriate analysis of a very low FF sample, which should fail an FF-based quality control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, depending on the software used for FF calculation, FF estimator accuracy can fall at low sequencing coverages in cases of truly low FFs ( Figs 3 and S6 ). Similar results were obtained by Miceikaitė et al ., who demonstrated that FF estimator accuracy tends to decrease at low sequencing depths [ 16 ]. Severe FF estimation inaccuracies can lead to the inappropriate analysis of a very low FF sample, which should fail an FF-based quality control.…”
Section: Discussionmentioning
confidence: 99%
“…That said, a similar downsampling approach was implemented successfully by Miceikaitė et al . in their investigation of FF estimation accuracy at low sequencing depths [ 16 ]. Our read placement variability effect analysis on Z-score inference was carried out only with the NIPTeR software, one of the most accurate tools in our comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Miceikaitė et al . demonstrating that FF estimator accuracy can decrease at low sequencing coverages (20). Severe FF estimation inaccuracies can lead to cases where a studied sample with a very low FF (which should fail the FF-based quality control) would be analysed, and the subsequent aneuploidy/euploidy estimation would be incorrectly considered as a confident estimate.…”
Section: Discussionmentioning
confidence: 99%
“…That said, a very similar downsampling approach has also been successfully implemented by Miceikaitė et al . to investigate fetal DNA fraction estimation accuracy at lower sequencing coverages (20). Our read placement variability effect analysis on Z-score inference was carried out only with the NIPTeR software, which nevertheless, was one of the most accurate tools in our comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the sequencing depth is too shallow, the number of read necessary to accurately estimate the ff is not reached and the sensibility and specificity of the test decreases. Higher sequencing depth (sd) can compensate for low ff, but a clear description of this relationship is missing [9] , [10] . There is no universal ff threshold applicable across sequencing platforms [4] , thus a solution allowing interlaboratory comparisons of quality parameters is missing.…”
Section: Introductionmentioning
confidence: 99%